Analysis of Solar Photovoltaic Module Waste: A Comparative Analysis of India and Global Best Practices - Uppal, Arunav (Digital Repository of Theses - SSBM Geneva, 2024)
While instrumental in advancing global sustainability efforts, the proliferation of solar photovoltaic (PV) technology has introduced significant challenges related to managing solar PV module waste. This thesis presents a rigorous comparative analysis of India's solar PV waste management practices, benchmarked against global best practices. The study systematically examines the awareness, practices, and challenges associated with solar PV waste management among key stakeholders in India, including manufacturers, regulators, and waste management professionals. The research is structured around critical questions concerning stakeholder awareness of the risks associated with solar PV waste, familiarity with recycling methods, and the efficacy of existing waste management systems. Furthermore, the study explores the influence of demographic variables—such as age, gender, industry affiliation, and years of experience—on these dimensions, testing a series of hypotheses to assess the significance of these relationships. Findings from this research reveal that, while demographic factors influence awareness and perceptions, they are not robust predictors of the challenges encountered in solar PV waste management. The challenges identified are pervasive across the industry, underscoring systemic issues that transcend specific demographic or industry segments. The study highlights substantial areas for improvement in India's current waste management infrastructure, regulatory frameworks, and technological capabilities. These gaps present significant barriers to effective solar PV waste management and suggest an urgent need for comprehensive policy reforms and the adoption of more sustainable practices. This study contributes to the broader discourse on environmental sustainability by offering a nuanced understanding of the complexities surrounding solar PV waste management in India. It also provides actionable recommendations for aligning India's practices with global standards, thereby enhancing the overall effectiveness of solar PV waste management efforts.